Photojournal: Venezuela - Yacher, L. (Focus on Geography, 2007)
Keywords: South America; Venezuela; dept.egm; imagery

Five new species of jaltomata (solanaceae) from cajamarca, peru - Mione, Thomas; Leiva, G Segundo; Yacher, Leon (Novon, 2007)
Five new suffrutescent to shrubby Jaltomata Schlechtendal species (Solanaceae) of the department of Cajamarca, Peru, are described and illustrated, Jaltomata contumacensis S. Leiva & Mione has a light green, urceolate-tubular corolla and grows in the province of Contumazá between 2530 and 3000 m; J. lanata S. Leiva & Mione has a whitish purple to pale purple, short-tubular corolla and grows in the province of San Pablo between 1850 and 2400 m; J. leivae Mione has a red-violet, urceolate corolla containing red nectar and grows in the province of Contumazá between 2560 and 2650 m; J. oppositifolia S. Leiva & Mione bas a white, broadly infundibular to rotate corolla and grows in province Chota between 2250 and 3090 m; and J. yacheri Mione & S. Leiva has a blue-purple, urceolate corolla and grows in province Hualgayoc at 3460 m. The fruits of two of these species are eaten by people.
Keywords: Edible fruit; Jaltomata; Magnoliophyta; Red nectar; Solanaceae; dept.egm